Development of an Integrated Digital Logbook with Problem-Based Learning (PBL) Student Worksheets in Motorcycle Engineering Instruction to Enhance Vocational Character in Vocational High School Students - Miftahussurur Miftahussurur; Yeri Sutopo (Journal of Vocational and Career Education, 2026)
This study was motivated by the need to strengthen vocational character, particularly discipline, technical competence, and problem-solving skills, among vocational high school students. Conventional paper-based workshop documentation has limited this process due to its vulnerability to manipulation and its inability to support real-time monitoring. This study aimed to develop and evaluate the feasibility, effectiveness, and practicality of an integrated digital logbook platform incorporating Problem-Based Learning (PBL)-based student worksheets for Motorcycle Engineering instruction at SMK Ma’arif NU 1 Cilongok. A Research and Development (R&D) approach using the ADDIE model was employed, consisting of Analysis, Design, Development, Implementation, and Evaluation phases. Data were collected through expert validation instruments, teacher and student practicality questionnaires, and vocational character observation rubrics. Instrument validity was analyzed using Aiken’s V, inter-rater reliability was examined using the Intraclass Correlation Coefficient (ICC), and platform effectiveness was evaluated using Normalized Gain (N-Gain) analysis and an independent-samples t-test. The results indicated that all research instruments met acceptable validity and reliability criteria, with Aiken’s V values ranging from 0.750 to 1.000 and ICC values ranging from 0.541 to 0.822. The platform effectively improved students’ vocational character, as demonstrated by a higher N-Gain score in the experimental group (0.6104; moderate category) compared with the control group (0.2760; low category), with a statistically significant difference (p < .001). The platform also demonstrated high practicality, receiving positive responses from teachers (87.02%) and students (86.64%). In conclusion, the PBL-integrated digital logbook platform was feasible, effective, and practical for supporting vocational learning. The platform provides a digital solution for improving workshop documentation management while fostering students’ self-regulation, discipline, and professional work habits aligned with industry expectations.